"The Increasing Number of Waria in Banda Aceh: Between Social Challenges and Law Enforcement" - Siti Zaviera; Mizaj Iskandar (QURU’: Journal of Family Law and Culture, 2025)
One of the things that is currently rife is the case of liwath or male to male intercourse with the willingness of both parties carried out by waria (female-male) or with a normal male appearance. In general, waria have no space in the religious and social spheres of society, because it goes back to the definition of waria itself which is in the middle between women and men. The region known as "serambi mekkah" has a special legal authority that is binding, namely Islamic law or called qanun. Qanun itself is still used today, one of which is Aceh Qanun Number. 6 of 2014 which regulates the jinayat law, jinayat is enforced to punish the perpetrators of khalwat, ikhtilath, and other adultery things that violate Islamic law. The purpose of this study is to examine whether there are legal facilities given to Aceh to implement legal actions and how the enforcement to date by the assigned parties. This research is a field research with qualitative method with empirical juridical approach. The result of this research is that the applicable legal position has been implemented as it should be and the winner of the transvestite contest who carries the name of Aceh is not domiciled in Aceh, while Qanun law applies where a person is located, so the Aceh government cannot give a warning or counselling as long as the transvestite is not in the Aceh area. Although there is a regulation of uqubat cambuk that may be applied to transvestites, the punishment can only be carried out if there is something that is violated, but if the transvestite is just living like an ordinary citizen, he cannot be subjected to this punishment because transvestites are a social disorder/disease, not something that violates positive legal rules, even though it is against Islamic law and occupies an area that applies Islamic law, but the right to live as an Indonesian citizen is still protected by Human Rights.